2020
DOI: 10.1111/eip.13021
|View full text |Cite
|
Sign up to set email alerts
|

Autistic traits in first‐episode psychosis: Rates and association with 1‐year recovery outcomes

Abstract: Aim: There is a growing appreciation that subthreshold but clinically elevated levels of autistic traits are clinically relevant. This study examined autistic traits in Singaporean patients with first-episode psychosis and their association with 1-year psychosis recovery. Methods:The relationship between baseline patient characteristics, autistic traits (measured with autism screening questionnaires) and psychosis recovery outcomes at 1-year were examined in 180 adults in the Early Intervention Psychosis Progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Stereotype endorsement and difficulty in communication skills indirectly affected recovery via depressive symptoms. Several recent studies have shown autistic traits in patients with psychotic disorders, including first-episode psychosis, which has been associated with poor recovery outcomes and social functioning [19,20,34]. Considering these previous findings and the results of our study, selfstigma and depression may partially be related to the association between high levels of autistic traits in patients with psychosis and poor recovery-related outcomes and social functioning.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Stereotype endorsement and difficulty in communication skills indirectly affected recovery via depressive symptoms. Several recent studies have shown autistic traits in patients with psychotic disorders, including first-episode psychosis, which has been associated with poor recovery outcomes and social functioning [19,20,34]. Considering these previous findings and the results of our study, selfstigma and depression may partially be related to the association between high levels of autistic traits in patients with psychosis and poor recovery-related outcomes and social functioning.…”
Section: Discussionsupporting
confidence: 80%
“…"I do not think so" to 4. "I very much think so," and five subscales (alienation [1,5,8,16,17,21], stereotype endorsement [2,6,10,18,19,23,24], perceived discrimination [3,15,22,25,26], social withdrawal [4,9,[11][12][13]20], and stigma resistance [7,14,[27][28][29]). The average ISMI score is interpreted as follows: 1.00-2.00, no or very mild self-stigma; 2.01-2.50, a mild level of self-stigma; 2.51-3.00, a moderate level of self-stigma; and 3.01-4.00, a severe level of self-stigma.…”
Section: Assessment Of Self-stigmamentioning
confidence: 99%
See 1 more Smart Citation
“…Zheng et al (2020) found that, at baseline, more ASD traits among FEP patients were associated with a greater likelihood of having “psychosis, not otherwise specified,” “mood disorder with psychotic features,” or “brief psychotic disorder” diagnoses, rather than a schizophrenia diagnosis. At 1 year follow‐up, more ASD traits in the same FEP group predicted lesss improvement in severity of psychotic symptoms or level of functioning.…”
Section: Resultsmentioning
confidence: 99%
“…There is limited data regarding autistic features in FEP and schizophrenia (Chisholm et al, 2019; Deste et al, 2018; Kästner et al, 2015; Zheng et al, 2021). Previous reports shed light on common clinical features in autism and schizophrenia although they are distinct clinical conditions.…”
Section: Discussionmentioning
confidence: 99%